Lattice Boltzmann Schemes with Relative Velocities (Communications in Computational Physics, 2018)
In this contribution, a new class of lattice Boltzmann schemes is introducedand studied. These schemes are presented in a framework that generalizes the multiplerelaxation times method of d'Humières. They extend also the Geier's cascadedmethod. The relaxation phase takes place in a moving frame involving a set of momentsdepending on a given relative velocity field. We establish with the Taylor expansionmethod that the equivalent partial differential equations are identical to theones obtained with the multiple relaxation times method up to the second order accuracy.The method is then performed to derive the equivalent equations up to thirdorder accuracy.